MIX PROPORTIONING OF SELF COMPACTING CONCRETE USING LIMESTONE POWDER - ZAINALDEEN, AVRAZ; QOJA, GHANIM HUSSEIN (Journal of Duhok University, 2021)
Self-compacting concrete (SCC) is a kind of concrete mixtures that can be used for placing in congested reinforcement structures without external vibrations. SCC has improved qualities and enhances concrete durability, working conditions, and productivity. This paper proposes an experimental procedure for the mix proportioning of SCC, considering M30 and M60 Grade concrete strength. Using limestone powder as a filler based on the aggregate packing principle and EFNRAC guideline for mix design. The tests that represent the properties of SCC in the plastic stage such as; V-funnel, slump flow, T500, L-Box, J-ring, and Sieve Segregation resistance were carried out. While in the hardened stage, the compressive strength was obtained at the ages of 7, 14, 28, and 56 days. The test results show that using 88 kg of limestone powder per unit volume can produce successfully SCC with compressive strength of 74.3 MPa at 56 days while using 225 kg of limestone powder produce SCC of compressive strength of 36.7 MPa at 56 days